Impact of COVID-19 pandemic on intensive care admissions and mortality due to self-poisoning: A retrospective comparative study from a tertiary care hospital - Aneela Α. Kidwai; Komal Fareed; Jamal Ara; Mahnoor Khalil; Shaista Ahmed; Syeda Urooj Riaz; Yumna Ahmed (Public Health and Toxicology)
Introduction COVID-19 struck the economies of every country, but the low- and middle-income countries had the most impact. Suicides during these times have increased, depicting the mental health of individuals. In this research, suicide rates and risk factors pre-COVID-19 and during the COVID-19 pandemic, as well as pre- and post-lockdown, were examined.